ENTREPRENEURSHIP EDUCATION IDEOLOGY IN ISLAM - azis azis abdullah; Sarwadi (Jurnal Al-Manar, 2022)
The foundation of Islamic education as the basis for Islamic education is Al Qur'an, Al Hadith Rasulullah Sholallahu alayhi wasalam. Islamic education in the course of its history is rife with various ideologies that have an impact on the quality of the resulting generation. Islam as a complete religion actually has given an ideological message that human nature is a servant as well as carrying out the mandate to manage, elaborate and optimize all natural and human potential. Entrepreneurship, education and economics eventually become an integral link to answer the message of the caliph to face an educational challenge in this era of disruption.